2021
DOI: 10.3390/healthcare9091220
|View full text |Cite
|
Sign up to set email alerts
|

Early Spatiotemporal Patterns and Population Characteristics of the COVID-19 Pandemic in Southeast Asia

Abstract: This observational study aims to investigate the early disease patterns of coronavirus disease 2019 (COVID-19) in Southeast Asia, consequently providing historical experience for further interventions. Data were extracted from official websites of the WHO and health authorities of relevant countries. A total of 1346 confirmed cases of COVID-19, with 217 recoveries and 18 deaths, were reported in Southeast Asia as of 16 March 2020. The basic reproductive number (R0) of COVID-19 in the region was estimated as 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…For example, on the site of Johns Hopkins University dedicated to COVID-19 [ 1 ], data clearly shows this influence on the case fatality rate corresponding to the cumulative deaths recorded 5 months after the beginning of the outbreak (12 May 2020) vs. the median age of many countries in 2017 ( Figure 1 ). This first observation has been confirmed by many studies in different countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] such as in France ( Figure 2 ), and we will confirm in this paper that the age of the patients suffering from COVID-19 is a good predictor of severity.…”
Section: Introductionsupporting
confidence: 85%
“…For example, on the site of Johns Hopkins University dedicated to COVID-19 [ 1 ], data clearly shows this influence on the case fatality rate corresponding to the cumulative deaths recorded 5 months after the beginning of the outbreak (12 May 2020) vs. the median age of many countries in 2017 ( Figure 1 ). This first observation has been confirmed by many studies in different countries [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] such as in France ( Figure 2 ), and we will confirm in this paper that the age of the patients suffering from COVID-19 is a good predictor of severity.…”
Section: Introductionsupporting
confidence: 85%
“…Therefore, the government can prepare mitigation measures for handling Covid-19 by emphasising cumulative cases and death rate conditions over provinces in Indonesia. Furthermore, in terms of VLN, the proportion of age group seems associated with the number of positive and death cases, which are also demonstrated by Zhu et al (2021). By the time the study report was written, the COVID-19 cases were predominantly caused by variant B.1.466.2, B.1.470, B.1.1.398 and B.1.459 (CNN Indonesia, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies using space-time scan for COVID-19 discovered that Hubei province has higher risk than the other region in China (42) whereas a Korean study found higher risk in Daegu City than neighboring province (43). A retrospective spatial scan study in Southeast Asia during January 13, 2020 and March 16, 2020 further confirmed that Malaysia and Singapore were the most likely cluster between March 4-March 16, 2020 (RR = 72.07, LLR = 1910.08, p < 0.001) (44). The most likely cluster for the period 2 (January 25 to October 8, 2020) consisted of Negeri Sembilan, Putrajaya, Kuala Lumpur, and Selangor (10 districts) in this study correlates with a state-level spatial scan analysis study in Malaysia (45).…”
Section: Discussionmentioning
confidence: 96%